2017
DOI: 10.14789/jmj.63.435
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease and Sleep

Abstract: Sleep is an important resting period, especially for the cardiovascular system, which has to work persistently.Therefore, qualitative and quantitative sleep disturbances can lead to cardiovascular disease (CVD). An inappropriate sleep duration, which leads to quantitative sleep impairments, and insomnia and sleep-disordered breathing (SDB), which result in quantitative/qualitative sleep impairments, are widely recognized to affect the incidence of CVD. Patients with CVD generally sleep less than the general po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Abbate et al showed in their systematic review that dietary intervention combined with exercise had the most beneficial effect on cardiovascular events as compared with diet or exercise intervention alone. Sleep and rest are also considered important target to combat NCDs [18,19]. Hill et al reported multiple components of the healthy lifestyle as mediators of the association between the purpose in life and health [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abbate et al showed in their systematic review that dietary intervention combined with exercise had the most beneficial effect on cardiovascular events as compared with diet or exercise intervention alone. Sleep and rest are also considered important target to combat NCDs [18,19]. Hill et al reported multiple components of the healthy lifestyle as mediators of the association between the purpose in life and health [34].…”
Section: Discussionmentioning
confidence: 99%
“…The rise in obesity has brought attention to lifestyle as a prominent cause of disease in modern times [16,17]. Recently, it has also been noted that there is growing evidence that quality and quantity of sleep are associated with NCDs such as cardiovascular diseases [18,19]. In addition, studies have shown that health-related lifestyle interventions are effective in reducing the incidence of many diseases including NCDs such as diabetes, coronary heart disease, and stroke [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep is an important resting period for the cardiovascular system, and impairments in sleep quality and quantity can thus lead to cardiovascular disease [1]. The quantitative impairments of sleep, such as short sleep duration, are reportedly associated with increased mortality [2].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative impairments of sleep are generally derived from insomnia including difficulties in initiating and maintaining sleep, both of which result in the impairment of daytime function [8], and from other sleep-related disorders, such as sleepdisordered breathing (SDB). Insomnia and SDB can deteriorate cardiovascular function [1,9] and are associated with increased incidence of cardiovascular disease including comorbidities, such as HF, acute coronary syndrome (ACS), or atrial fibrillation (AF) [10][11][12][13], and consequently with enhanced mortality [14,15]. Patients with HF reportedly have approximately 4-12 min longer sleep onset latency and 70 min shorter total sleep time than healthy controls [16].…”
Section: Introductionmentioning
confidence: 99%